Early-stage heart failure with preserved ejection fraction in the pig: a cardiovascular magnetic resonance study. Issue 1 (December 2016) - Reiter, Ursula; Reiter, Gert; Manninger, Martin; Adelsmayr, Gabriel; Schipke, Julia; Alogna, Alessio; Rajces, Alexandra; Stalder, Aurelien; Greiser, Andreas; Mühlfeld, Christian; Scherr, Daniel; Post, Heiner; et al.
Abstract Background The hypertensive deoxy-corticosterone acetate (DOCA)-salt-treated pig (hereafter, DOCA pig) was recently introduced as large animal model for early-stage heart failure with preserved ejection fraction (HFpEF). The aim of the present study was to evaluate cardiovascular magnetic resonance (CMR) of DOCA pigs and weight-matched control pigs to characterize ventricular, atrial and myocardial structure and function of this phenotype model. Methods Five anesthetized DOCA and seven control pigs underwent 3 T CMR at rest and during dobutamine stress. Left ventricular/atrial (LV/LA) function and myocardial mass (LVMM), strains and torsion were evaluated from (tagged) cine imaging. 4D phase-contrast measurements were used to assess blood flow and peak velocities, including transmitral early-diastolic (E) and myocardial tissue (E') velocities and coronary sinus blood flow. Myocardial perfusion reserve was estimated from stress-to-rest time-averaged coronary sinus flow. Global native myocardial T1 times were derived from prototype modified Look-Locker inversion-recovery (MOLLI) short-axis T1 maps. After in-vivo measurements, transmural biopsies were collected for stereological evaluation including the volume fractions of interstitium (VV (int/LV)) and collagen (VV (coll/LV)). Rest, stress, and stress-to-rest differences of cardiac and myocardial parameters in DOCA and control animals were compared byt -test. Results In DOCA pigs LVMM (p  < 0.001) and LV wall-thickness (end-systole/end-diastole, p  = 0.003/p  = 0.007) were elevated. During stress, increase of LV ejection-fraction and decrease of end-systolic volume accounted for normal contractility reserves in DOCA and control pigs. Rest-to-stress differences of cardiac index (p  = 0.040) and end-diastolic volume (p  = 0.042) were documented. Maximal (p  = 0.042) and minimal (p  = 0.012) LA volumes in DOCA pigs were elevated at rest; total LA ejection-fraction decreased during stress (p  = 0.006). E' was lower in DOCA pigs, corresponding to higher E/E' at rest (p  = 0.013) and stress (p  = 0.026). Myocardial perfusion reserve was reduced in DOCA pigs (p  = 0.031). T1-times and VV (int/LV) did not differ between groups, whereas VV (coll/LV) levels were higher in DOCA pigs (p  = 0.044). Conclusions LA enlargement, E' and E/E' were the markers that showed the most pronounced differences between DOCA and control pigs at rest. Inadequate increase of myocardial perfusion reserve during stress might represent a metrics for early-stage HFpEF. Myocardial T1 mapping could not detect elevated levels of myocardial collagen in this model. Trial registration The study was approved by the local Bioethics Committee of Vienna, Austria (BMWF-66.010/0091-II/3b/2013).